2023
DOI: 10.2337/dc22-1993
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Consumption and Risk of Type 2 Diabetes: Three Large Prospective U.S. Cohort Studies

Abstract: OBJECTIVE We examined the relationship between ultra-processed food (UPF) intake and type 2 diabetes (T2D) risk among 3 large U.S. cohorts, conducted a meta-analysis of prospective cohort studies, and assessed meta-evidence quality. RESEARCH DESIGN AND METHODS We included 71,871 women from the Nurses’ Health Study, 87,918 women from the Nurses’ Health Study II, and 38,847 men from the Health Professional Follow-Up Study. Diet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 37 publications
5
50
0
Order By: Relevance
“…The systematic search identified 430 de-duplicated articles (fig 1). After applying the eligibility criteria, we included 14 meta-analysis studies with 45 distinct pooled analyses 1718404142434445464748495051…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic search identified 430 de-duplicated articles (fig 1). After applying the eligibility criteria, we included 14 meta-analysis studies with 45 distinct pooled analyses 1718404142434445464748495051…”
Section: Resultsmentioning
confidence: 99%
“…Each of the meta-analysis studies examined the non-dose-response associations between exposure to ultra-processed foods and adverse health outcomes. However, an additional analysis involving dose-response modelling of the ultra-processed food exposure variable was conducted in 13 pooled analyses across five meta-analysis studies 4042434751. The outcomes considered using this approach included all cause mortality and cardiovascular disease events, such as cardiovascular disease morbidity and mortality, associated with each increase in daily servings of ultra-processed food 43.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] In fact, a recent study has shown that distinct subgroups of UPF are differently associated with type-2 diabetes risk, with subgroups such as fruit-and dairybased ultra-processed desserts even showing a risk reduction. 39 Another study found that although UPF consumption was associated with multimorbidity related to cancer and cardiometabolic diseases, this association was not seen in the subgroup of plantbased UPF, 40 suggesting that Nova may not capture possible nuance in "quality" among different UPF. In our study, textured soy protein was an important contributor to UPF consumption.…”
Section: Discussionmentioning
confidence: 99%
“…5 Globalization of the Western diet in the form of ultraprocessed food in the last few years has led to obesity and DM. 6 The public's lack of awareness and oblivious attitude is a well-established factor in the escalation of the DM rate in Pakistan. 7 Unequal access to insulin, especially in low-and middle-income countries due to the lack of government policies on the selection of insulin, standardization of prices, and compensation, has created a gap in the effective management of DM.…”
mentioning
confidence: 99%